Development Strategies for Sharia-Based Early Childhood Educational Institutions: A Strategic Management Approach to Institutional Quality - Maulani Khairunnisa Pulungan; Isra Hayati (Journal of Educational Management Research, 2026)
This study aims to analyze the development strategies of Sharia-based educational institutions by examining strategic management practices, curriculum implementation, human resource development, organizational culture, and quality improvement efforts. This study employed a qualitative descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving participants who were directly engaged in institutional management and educational implementation. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion verification. The findings reveal that the development of Sharia-based educational institutions is implemented through systematic strategic planning, the integration of Islamic values into curriculum and learning activities, continuous teacher professional development, and the strengthening of an Islamic organizational culture. The study also found that leadership commitment, teacher competence, parental involvement, and effective communication contribute significantly to improving educational quality. The implication of this study is that strategic management based on Islamic values can serve as a sustainable framework for strengthening institutional quality, improving educational services, and supporting the development of Sharia-based educational institutions in response to contemporary educational challenges.